A community-based survey of visible congenital anomalies in rural Tamil Nadu - K. Sridhar (Indian Journal of Plastic Surgery)
An extensive community-based survey of visible congenital defects covering 12.8 million children in rural Tamil Nadu state was conducted during the years 2004OE05. A door-to-door survey was done utilizing the existing health care delivery system. More than 10,000 village health nurses were involved to collect the data. All children between the ages of 0 and 15 years were seen. The children with defects were seen by a medical officer and diagnosis was made as per chart. A total of 1.30% of children were born with some visible anomalies. The male:female ratio was 1.3:1. There was a family history in 9% and consanguinity in 32%. More than 5% mothers had taken some medication in the first trimester of pregnancy out of which anti-convulsants were 3.4%. Facial clefts showed a lower incidence of 1 in 1976 live births with peak incidence between March and June. Cleft palate alone showed a higher percentage (30%) than other studies.